2017
DOI: 10.1098/rspb.2016.2654
|View full text |Cite
|
Sign up to set email alerts
|

Social foraging and individual consistency in following behaviour: testing the information centre hypothesis in free-ranging vultures

Abstract: One contribution of 17 to a theme issue 'Moving in a moving medium: new perspectives on flight'. Natural selection theory suggests that mobile animals trade off time, energy and risk costs with food, safety and other pay-offs obtained by movement. We examined how birds make movement decisions by integrating aspects of flight biomechanics, movement ecology and behaviour in a hierarchical framework investigating flight track variation across several spatio-temporal scales. Using extensive global positioning syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 64 publications
1
97
0
Order By: Relevance
“…In colonial species, this is promoted by the breeding site functioning as an information centre (Harel et al . ). Previous studies showed predator specialisation on resources that are temporally dynamic but predictable in space and/or time.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In colonial species, this is promoted by the breeding site functioning as an information centre (Harel et al . ). Previous studies showed predator specialisation on resources that are temporally dynamic but predictable in space and/or time.…”
Section: Introductionmentioning
confidence: 97%
“…Individuals may overcome low spatio-temporal prey predictability by diversifying their diet, either through generalist foraging tactics (no selection) or by alternating foraging tactics targeting specific prey items (narrow short-term resource selection). In colonial species, this is promoted by the breeding site functioning as an information centre (Harel et al 2017). Previous studies showed predator specialisation on resources that are temporally dynamic but predictable in space and/or time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigation of dependencies among species, where one species acts as a scout that produces information used by individuals of another species (e.g., lappet-faced and African white-backed vultures [70], eagles and Gyps vultures [58] or avian and mammalian scavengers [100]) illustrate how changes in community structure (e.g., local extinctions) can impact the fate of community members. A positive feedback loop, in which decreasing densities reduce the ability of the remaining individuals to find and/or access resources, can explain frequent population collapses in this guild [14,21,100]. Overall, this integration of approaches (observational, experimental, and modeling) provides insight into the role of social information in driving correlated behaviors in scavenger communities, offering tools to mitigate the detrimental effects of environmental change on the populations and communities of these sanitation providers.…”
Section: Box 1 Social Information Sharing Among Foraging Scavengersmentioning
confidence: 99%
“…Here, we show that social information-mediated positive density dependence can readily extend beyond populations to communities, when information is shared across species. Positive density dependence can not only lead to rapid population growth, but [ 2 8 9 _ T D $ D I F F ] can also create critical thresholds, below which the population or community is prone to sudden collapse [14,27,33,35]. The latter consequence arises because the loss of individuals is increasingly detrimental to the survival or reproductive rate of those that remain, a phenomenon that has been shown experimentally to cause collapse in laboratory-based yeast populations [37,38] ( Figure 2).…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation